2020
DOI: 10.1080/02670836.2020.1777509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cobalt on mechanical properties of high silicon ductile irons

Abstract: High silicon ductile irons are being developed due to their advantages relating to pearlitic-ferritic grades (high ductility, fully ferritic structures, good machinability, etc.). Recent studies reported that silicon contents higher than 5.2 wt.% originates drastic embrittlement due to chemical ordering. For improving the mechanical properties, addition of other alloying elements becomes an interesting way of work. This study focuses on the cobalt effect on as-cast microstructures and mechanical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…All the cobalt bearing alloys resulted in higher levels of degenerate graphite (Table 5.5). This finding was also reported by González-Martínez et al who observed that cobalt deteriorates the graphite shape and increases the tendency to CHG formation [67]. Early crack initiation can start from degenerated graphite nodules, given the notch effect on graphite nodules in ductile iron, which results in lower fracture toughness [125], [126].…”
Section: Influence Of Cobalt In the Impact Propertiessupporting
confidence: 79%
See 4 more Smart Citations
“…All the cobalt bearing alloys resulted in higher levels of degenerate graphite (Table 5.5). This finding was also reported by González-Martínez et al who observed that cobalt deteriorates the graphite shape and increases the tendency to CHG formation [67]. Early crack initiation can start from degenerated graphite nodules, given the notch effect on graphite nodules in ductile iron, which results in lower fracture toughness [125], [126].…”
Section: Influence Of Cobalt In the Impact Propertiessupporting
confidence: 79%
“…A study of Fe-Si-Co alloys has shown that in addition to the B2 and D03 ordered phases that were discussed in Chapter 2, a two-phase region (B2+D03) exists between these phases, which cobalt shifting the transition between disordered (A2-phase) to ordered (B2-phase) to lower silicon values [128]. This behavior was observed by González-Martínez et al, who found that the maximum tensile strength for cobalt-bearing alloys was around 4.3-4.4 wt.% Si versus 5.2 wt.% Si for alloys without cobalt, attributing the brittleness of these alloys to the presence of ordered phases [67]. For this reason, x-ray diffraction (XRD) was performed on the 4 wt.% Co sample to look for the presence of ordered phases.…”
Section: Influence Of Cobalt In the Impact Propertiesmentioning
confidence: 59%
See 3 more Smart Citations